Adiposity in Schizophrenia: A Systematic Review and Meta-Analysis. (September 2021) - Smith, E.; Singh, R.; Lee, J.; Colucci, L.; Graff-Guerrero, A.; Remington, G.; Hahn, M.; Agarwal, S.M.
Abstract : Background: Despite an established relationship between schizophrenia (SCZ), antipsychotic (AP) medication, and metabolic dysregulation, the effect of these aspects on visceral adiposity is less well understood. Methods: To fill this gap, we searched MEDLINE, EMBASE, PsychINFO and Scopus for all relevant case-control and prospective longitudinal studies using imaging techniques from inception until February 2021. Percent body fat (%BF), subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) were analyzed as primary outcomes. Results: A random-effects meta-analysis of 29 identified studies revealed that patients have greater %BF (mean difference (MD)=3.09%, p=0.010), SAT (MD=24.29 cm 2, p=0.03) and VAT (MD=33.73 cm 2, p=0.03) compared to healthy controls. AP treatment was found to increase SAT (MD=31.98 cm 2, p=0.002) and VAT (MD=16.30 cm 2, p<0.0001). Change in %BF was higher for AP-free/AP-naïve patients compared to treated patients (p=0.02). Conclusion: Patients with SCZ spectrum disorders have greater adiposity than healthy controls, which is increased by AP treatment. Our findings highlight a need for increased monitoring and earlier treatment of metabolic dysfunction in this population.